Novel catalysts with multivalence copper for organic pollutants removal from wastewater with excellent selectivity and stability in Fenton‐like process under neutral pH conditions. (5th December 2022) - Li, Haitao; Liu, Xiang; Chen, Xueli; Chen, Yonglin; Li, Yuping; Motkuri, Radha Kishan; Dai, Zhongde; Kumar, Abhishek; Fang, Tian; Shen, Jian
Abstract: Fenton‐like reaction has been widely used for organics degradation. However, most Fenton‐like reaction works at low pH range (pH < 4) with uncontrollable selectivity of hydroxyl radicals from H2 O2 activation, and unsatisfied catalyst stability, which is compromised advanced oxidation performance for water/wastewater treatments. In this work, to solve the drawbacks, novel copper catalysts were fabricated via hydrogen reduction/calcination of Cu 2+ ‐supported Al/MCM‐41 with precisely controllable copper valence state. Compared with catalysts with monovalence copper (i.e., CuO, Cu, and Cu 2+ ), the obtained catalysts with multivalence copper present higher selectivity, excellent stability towards OH radical pathways, and outperformance in p CBA degradation efficiency at neutral state. In addition, the fabricated catalysts also exhibited excellent phenol removal efficiency (75.5%) and H2 O2 utilization efficiency (47.9%) within neutral environment. Moreover, the degradation efficiency of phenol approaches to 100% within only 2 h. The catalyst also shows good stability for organic pollutants removal, which shows good potential in catalytic oxidation for phenolic compounds‐containing wastewater in Fenton‐like reaction, especially under neutral pH conditions. Practitioner Points: Multivalence copper presents great potentials for organic compounds removal at neutral condition. Multivalence copper shows higher selectivity toward OH and good stability at neutral condition. Multivalence copper exhibiters outperformed phenol removal efficiency at neutral condition. Abstract : Catalyst with multivalence copper presents higher selectivity, excellent stability towards OH radical pathways, and outperformance in p CBA degradation efficiency at neutral state. In addition, it also exhibited excellent phenol removal efficiency (75.5%) and H2 O2 utilization efficiency (47.9%) within neutral environment in Fenton‐like reaction.